THE IMPORTANCE OF SOCIO-PHILOSOPHICAL FACTORS, VALUES, AND GENDER JUSTICE IN SHAPING WOMEN’S INTELLECTUAL AND SPIRITUAL POTENTIAL IN NEW UZBEKISTAN (Scientific journal of the Fergana State University, 2026)
The article analyzes the role of socio-philosophical factors in shaping women’s intellectual and spiritual potential in the context of New Uzbekistan. The study highlights the value system, social consciousness, principles of gender justice, education and cultural paradigms, as well as the challenges of the digital society as key factors influencing the intellectual development of women. Additionally, the importance of developing women’s scientific, creative, and political activity, digital competencies, and professional skills is emphasized from both philosophical and social perspectives.